2012
DOI: 10.1007/s10517-012-1896-0
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Detection of Mesenchymal Stem Cells in the Kidneys during Therapy of Experimental Renal Pathologies

Abstract: We studied the possibility of using different methods for identification of mesenchymal multipotent stromal cells in the renal parenchyma under conditions of experimental thermal ischemia of the kidneys and acute pyelonephritis. In vivo and in vitro methods of identification of mesenchymal multipotent stromal cells by magnetic resonance imaging and immunological and immunohistochemical methods were compared. Labeling of stem cells with iron-containing particles followed by their histological identification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[10][11][12] Experimental studies in rat models have demonstrated the potential efficacy of fetal stem cells in treating liver diseases, kidney diseases, and diseases of the central nervous system. [13][14][15][16][17] The therapeutic effects of fetal stem cell may be related directly to embryo-specific growth factors, cytokines, and other signaling molecules that are able to activate recovery and survival in the recipient's own cells. 11 It is believed that introducing suspensions of fetal cells into the patient using network signaling can activate specialized and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Experimental studies in rat models have demonstrated the potential efficacy of fetal stem cells in treating liver diseases, kidney diseases, and diseases of the central nervous system. [13][14][15][16][17] The therapeutic effects of fetal stem cell may be related directly to embryo-specific growth factors, cytokines, and other signaling molecules that are able to activate recovery and survival in the recipient's own cells. 11 It is believed that introducing suspensions of fetal cells into the patient using network signaling can activate specialized and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%